Homo-PROTACs for the Chemical Knockdown of Cereblon - Steinebach, Christian; Lindner, Stefanie; Udeshi, Namrata D; Mani, Deepak C; Kehm, Hannes; Köpff, Simon; Carr, Steven A; Gütschow, Michael; Krönke, Jan (ACS chemical biology, 2018)
The immunomodulatory drugs (IMiDs) thalidomide, lenalidomide, and pomalidomide, all approved for the treatment of multiple myeloma, induce targeted ubiquitination and degradation of Ikaros (IKZF1) and Aiolos (IKZF3) via the cereblon (CRBN) E3 ubiquitin ligase. IMiD-based proteolysis-targeting chimeras (PROTACs) can efficiently recruit CRBN to a protein of interest, leading to its ubiquitination and proteasomal degradation. By linking two pomalidomide molecules, we designed homobifunctional, so-called homo-PROTACs and investigated their ability to induce self-directed ubiquitination and degradation. The homodimerized compound 15a was characterized as a highly potent and efficient CRBN degrader with only minimal effects on IKZF1 and IKZF3. The cellular selectivity of 15a for CRBN degradation was confirmed at the proteome level by quantitative mass spectrometry. Inactivation by compound 15a did not affect proliferation of different cell lines, prevented pomalidomide-induced degradation of IKZF1 and IKZF3, and antagonized the effects of pomalidomide on multiple myeloma cells. Homobifunctional CRBN degraders will be useful tools for future biomedical investigations of CRBN-related signaling and may help to further elucidate the molecular mechanism of thalidomide analogues.